Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/pon.3447
|View full text |Cite
|
Sign up to set email alerts
|

Is implementing screening for distress an efficient means to recruit patients to a psychological intervention trial?

Abstract: Implementing screening proved inefficient for recruiting distressed cancer patients post-treatment to a randomized controlled trial on PST, with need for services being much less than anticipated. Consecutively screening patients did not result in a sample representative of the larger pool of distressed patients, which may lower generalizability. An adequately powered intervention trial using screening requires a feasibility study establishing recruitment rates and dedicated, funded staff assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 49 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…Although the percentage of patients with psychiatric disorder having received mental health care was higher than reported previously (57.3 vs 43.6), about half of patients with psychiatric disorder did not use mental health care. This is in line with research demonstrating that there is no one‐on‐one relationship between positive screen for psychological distress and subsequent wish for or use of mental health care . For example, distressed patients could also choose to rely on family or prefer to not talk about it .…”
Section: Discussionsupporting
confidence: 80%
“…Although the percentage of patients with psychiatric disorder having received mental health care was higher than reported previously (57.3 vs 43.6), about half of patients with psychiatric disorder did not use mental health care. This is in line with research demonstrating that there is no one‐on‐one relationship between positive screen for psychological distress and subsequent wish for or use of mental health care . For example, distressed patients could also choose to rely on family or prefer to not talk about it .…”
Section: Discussionsupporting
confidence: 80%
“…In our study, almost one in three depressed persons reported no need or time for treatment. Several studies have drawn similar conclusions that cancer patients with elevated symptoms did not want a referral . Possible reasons that have been identified include patients' desire to manage problems on their own or by means of informal social support, which may be related to fear of stigmatization for visiting a psychologist .…”
Section: Discussionmentioning
confidence: 88%
“…Only 1.0% of the approached individuals participated in the RCT. Several other trials on psychological outcomes in oncology also found low inclusion rates between 2.5% and 3.5% . Above‐mentioned trials and our trial used consecutive sampling for patient recruitment, which encompasses systematically screening every individual who meets the selection criteria .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Methodological factors include the use of screening instruments that have low predictive validity and do not succeed in identifying those patients who desire supportive psychosocial care, as well as inefficient procedures for approaching cancer survivors. An example of the first factor was provided by van Scheppingen and colleagues who conducted an RCT investigating the efficacy of problem‐solving therapy for cancer survivors. They reported that screening based on symptom checklist scores and 1 additional question on need for services proved unsuccessful for recruiting sufficient cancer patients in need of care.…”
mentioning
confidence: 99%